Increased Expression of Rififylin in A < 330 Kb Congenic Strain is Linked to Impaired Endosomal Recycling in Proximal Tubules - Joe, Bina; Gopalakrishnan, Kathirvel; Kumarasamy, Sivarajan; Yan, Yanling; Liu, Jiang; Kalinoski, Andrea L.; Kodandapani, Anbarasi; Farms, Phyllis (Frontiers in Genetics, 2012)
Cell surface proteins are internalized into the cell through endocytosis and either degraded within lysosomes or recycled back to the plasma membrane. While perturbations in endosomal internalization are known to modulate renal function, it is not known whether similar alterations in recycling affect renal function. Rififylin is a known regulator of endocytic recycling with E3 ubiquitin protein ligase activity. In this study, using two genetically similar strains, the Dahl Salt-sensitive rat and an S.LEW congenic strain, which had allelic variants within a <330kb segment containing rififylin, we tested the hypothesis that alterations in endosomal recycling affect renal function. The congenic strain had 1.59 fold higher renal expression of rififylin. Transcriptome analysis indicated that components of both endocytosis and recycling were upregulated in the congenic strain. Transcription of Atp1a1 and cell surface content of the protein product of Atp1a1, the alpha subunit of Na+K+ATPase were increased in the proximal tubules from the congenic strain. Because rififylin does not directly regulate endocytosis and it is also a differentially expressed gene within the congenic segment, we reasoned that the observed alterations in the transcriptome of the congenic strain constitute a feedback response to the primary functional alteration in recycling caused by rififylin. To test this, recycling of transferrin was studied in isolated proximal tubules. Recycling was significantly delayed within isolated proximal tubules of the congenic strain, which also had a higher level of polyubiquitinated proteins and proteinuria compared with S. These data provide evidence to suggest that delayed endosomal recycling caused by excess of rififylin indirectly affects endocytosis, enhances intracellular protein polyubiquitination and contributes to proteinuria.